2020
DOI: 10.1186/s13059-020-02064-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome and antigen-immunoglobin analysis reveals the diversity of B cells in non-small cell lung cancer

Abstract: Background Malignant transformation and progression of cancer are driven by the co-evolution of cancer cells and their dysregulated tumor microenvironment (TME). Recent studies on immunotherapy demonstrate the efficacy in reverting the anti-tumoral function of T cells, highlighting the therapeutic potential in targeting certain cell types in TME. However, the functions of other immune cell types remain largely unexplored. Results We conduct a single-cell RNA-seq analysis of cells isolated from tumor tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 46 publications
4
120
0
Order By: Relevance
“…To find interactions across multiple genes and cells, analysis and visualisation of this high dimensional single-cell data is facilitated by clustering and nonlinear dimensionality reduction algorithms [e.g., t-distributed stochastic neighbor embedding (t-SNE) or Uniform Manifold Approximation and Projection (UMAP)] 21,22 . scSeq of transcriptomes has been used extensively to profile the gene expression signatures of T and B cells to identify novel cellular subsets and phenotypes as well as their response to vaccination, infection and cancer [23][24][25][26] . Furthermore, clustering with scSeq data enables the unbiased identification of cellular states and analyses of the broad continuum of T and B cell populations as well as their differentiation trajectories 27 .…”
Section: Introductionmentioning
confidence: 99%
“…To find interactions across multiple genes and cells, analysis and visualisation of this high dimensional single-cell data is facilitated by clustering and nonlinear dimensionality reduction algorithms [e.g., t-distributed stochastic neighbor embedding (t-SNE) or Uniform Manifold Approximation and Projection (UMAP)] 21,22 . scSeq of transcriptomes has been used extensively to profile the gene expression signatures of T and B cells to identify novel cellular subsets and phenotypes as well as their response to vaccination, infection and cancer [23][24][25][26] . Furthermore, clustering with scSeq data enables the unbiased identification of cellular states and analyses of the broad continuum of T and B cell populations as well as their differentiation trajectories 27 .…”
Section: Introductionmentioning
confidence: 99%
“…BTNL9 on B cells (naïve B cells) was not correlated with normal adjacent tissues but was signi cantly correlated with LUAD tissues, except for plasma B cells, suggesting that BTNL9 regulates the function of naïve B cells in TME. Previous studies have also shown that naïve B cells are down-regulated in advanced NSCLC and are related to poor prognosis [36]. Furthermore, CARE database analysis showed that BTNL9 expression is to be associated with effective target therapy response ( Fig.…”
Section: Discussionmentioning
confidence: 83%
“…GEPIA database analysis found that normal lung tissue was not correlated with DC and its subtypes cDCs1 and cDCs2, but was signi cantly positively correlated with LUAD ( Table 2), indicating that all DCs regulated by BTNL9 may participate in the LUAD immune response. B cells are heterogeneous, and include two subtypes: naïve B cells and plasma B cells [36]. TIMER analysis found that total B cells and naïve B cells were signi cantly related to BTNL9 expression before and after purity adjustment, but plasma B cells were not correlated to BTNL9 expression before and after purity adjustment.…”
Section: Correlation Between Btnl9 and Markers Of In Ltrating Immunementioning
confidence: 98%
“…13 However, this method is now mainly used to analyze T cells in the tumor microenvironment, while tumor-infiltrating B cells have been largely ignored. In a study recently published in Genome Biology, titled "Single-cell transcriptome and antigenimmunoglobin analysis reveals the diversity of B cells in non-small cell lung cancer", 14 By analyzing the conditioned medium of plasma-like B cells from different stages of NSCLC, the authors found that plasma-like B cells from different stages had different effects on tumor cells and these effects mainly depends on the IgGs they secreted. In order to illustrate the biological functions of these IgGs, the authors identified their target proteins through immunoprecipitation assay.…”
mentioning
confidence: 99%
“…However, this method is now mainly used to analyze T cells in the tumor microenvironment, while tumor‐infiltrating B cells have been largely ignored. In a study recently published in Genome Biology , titled “Single‐cell transcriptome and antigen‐immunoglobin analysis reveals the diversity of B cells in non‐small cell lung cancer”, 14 Chen et al . from China examined the tumor‐infiltrating B cell profiles from NSCLC patients by single‐cell RNA‐sequencing and analyzed the relationship between the sequencing results and the prognosis of participants.…”
mentioning
confidence: 99%